2017
DOI: 10.1101/189944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indexing sensory plasticity: Evidence for distinct Predictive Coding and Hebbian Learning mechanisms in the cerebral cortex

Abstract: Highlights:• ERP and DCM study of two sensory plasticity paradigms: roving MMN and visual LTP• First demonstration of multiple learning mechanisms under different task demands• Evidence for both Predictive Coding and Hebbian learning mechanisms• The BDNF Val66Met polymorphism modulates ERPs for both paradigms• However, the polymorphism only modulates MMN network connectivity not peer-reviewed) is the author/funder. All rights reserved. No reuse allowed without permission.The copyright holder for this preprint … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…This effect was seen in the comparisons between all three groups in the late post-tetanus block, and between Val homozygotes and Met carriers in the early post-tetanus block. Spriggs et al (2017b) 1 also found that the Val 66 Met polymorphism impacted the magnitude of visual LTP, with genotype differences in the P2 component of the VEP (greater shift in Met carriers) 2 . It will therefore be important for further studies to characterise the complex relationship between the BDNF Val 66 Met polymorphism and visual LTP.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This effect was seen in the comparisons between all three groups in the late post-tetanus block, and between Val homozygotes and Met carriers in the early post-tetanus block. Spriggs et al (2017b) 1 also found that the Val 66 Met polymorphism impacted the magnitude of visual LTP, with genotype differences in the P2 component of the VEP (greater shift in Met carriers) 2 . It will therefore be important for further studies to characterise the complex relationship between the BDNF Val 66 Met polymorphism and visual LTP.…”
Section: Discussionmentioning
confidence: 97%
“… 2 While the results of these two studies may seem contradictory, there are significant differences in the approaches taken between them. First, Spriggs et al (2017b) grouped Met homozygotes and heterozygotes together into a “Met Carrier” group, thus overshadowing the dosage effect seen in the late post-tetanus block of the current study. Additionally, the current study employed previously established analysis methods and specifically focused on the N1b.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The intrinsic connectivities are shown in Figure 1a; note the excitatory conductances based on AMPA and NMDA and inhibitory GABA-A and GABA-B conductances. The model is an extension of the SPM conductancebased CMM model (SPM12, 2013): inclusion of separate supragranular and infragranular interneuron populations creates a more biophysically realistic model that allows a greater flexibility of independence of deep and superficial activity than in previous work (Bhatt et al, 2016;Shaw et al, 2019;Spriggs et al, 2018). Additionally, the new 'tp' population expressed a hyperpolarization-activated cation current (H-current) and a non-inactivating potassium current (M-current) to provide surrogate intrinsic dynamics involved in the characteristic intrinsic bursting behavior of these cells.…”
Section: Neuronal Modeling: An Extended Canonical Microcircuit Modelmentioning
confidence: 99%
“…Using parametric empirical Bayes to optimize the model across participants and drug conditions we examined how modeled GABAergic dynamics are altered by tiagabine. Based on the hypothesis that prediction and prediction error depend onshort-termGABAergicplasticity (Castro-Alamancos and Connors, 1996;Garrido et al, 2009a;Mongillo et al, 2018;Spriggs et al, 2018), we predicted that upper and lower hierarchical frontotemporal processing would be differentially affected by tiagabine during standard and deviant tones.…”
Section: Introductionmentioning
confidence: 99%